High-efficiency p-i-n a-Si:H solar cells with low boron cross-contamination prepared in a large-area single-chamber PECVD reactor - Kroll, U.; Bucher, C.; Benagli, S.; Schönbächler, Isabelle; Meier, Johannes; Shah, Arvind; Ballutaud, J.; Howling, A. A.; Hollenstein, C.; Buechel, A.; Poppeller, M. (My University, 2004)
In this work, a new type of short water vapor treatment of the interface between the p- and i-layer is presented. This novel treatment is performed under vacuum below 1 mbar for 5 min and considerably reduces the i-layer boron contamination in amorphous silicon (a-Si:H) p-i-n solar cells prepared in single-chamber reactors. A significant advantage is that the substrate with the p-layer can remain loaded in the reactor during this oxidation treatment. The high effectiveness of this treatment in reducing the boron cross-contamination is directly supported by secondary ion mass spectroscopy measurements, by tracing the boron concentration depth profile across the p–i interface and by quantum efficiency measurements of the deposited cells. By applying this water vapor treatment, 0.3-μm-thick a-Si:H p-i-n solar cells of 1 cm2 with high initial conversion efficiencies of 10.1% are deposited in a commercial large-area (35×45 cm2) single-chamber PECVD KAI™ reactor and can clearly compete with cells deposited in multi-chamber systems. Light soaking of these cells for 1200 h at 50 °C leads to stabilized efficiencies of 8.2%. The relative typical efficiency degradation of 20% of such 0.3-μm-thick single-junction cells demonstrates that this treatment does not affect the stability in a negative manner.
Keywords: amorphous silicon; solar cells; boron contamination; PECVD; single-chamber process